Arrestment of the estuarine plume in Maputo bay, Mozambique - Markull, Katrin (2018)
Maputo Bay is a tidally-energetic embayment in Mozambique, influenced by strong rainfall and associated river runoff during the wet season. Previous investigations have suggested the arrestment of the freshwater plume related to high mixing during spring tide, eroding stratification and preventing an efficient exchange with the shelf due to the hampering of density currents. It was suggested that, with decreasing mixing towards neap tide, the bay would re-stratify, releasing the estuarine plume. The objective of this dissertation was to find out whether and under which conditions this arrestment of the estuarine plume occurs in Maputo Bay. A 3-dimensional hydrodynamic model was applied to the bay, improving a previously published model through vertical and temporal refinement and recalibration. It is shown that now the model reproduces more accurately the semidiurnal and fortnightly stratification-mixing cycles occurring during the wet season. However, the model still predicts salinities lower than those found in observations. Uncertainties increase towards the mouth of the Maputo River, for which only modelled river flow data was available to force the bay dynamics, indicating this input as a possible source of the underestimation of salinity. The effect of varying river discharges, varying timings of discharge as well as varying discharge ratios on flushing times was investigated through a set of experiments of varying Maputo and Incomati river flows as well as timings of discharge during the spring-neap cycle. The results suggest that when no discharge or a small discharge is introduced, flushing times are smallest during spring tide, when barotropic forcing is strong. Largest flushing times are found approximately 40 hours before neap tide, when tidal forcing is relatively weak. Flushing times for model runs with larger discharge were smaller due to the addition of flushing from river water. Here, flushing times were especially small during neap tide, when the decreased tidal mixing lead to stratification through which a classical estuarine circulation could develop, leading to an efficient bay-shelf exchange. Maximum flushing times for high-discharge runs during wet season were found for spring tide. Shelf-bay exchange was most efficient when the discharge of the Maputo River was larger than the discharge of the Incomati River, due to its location opposite the bay opening, thus influencing a larger area before leaving the bay. Timing of the discharge of the freshwater had only small effects, influencing the amount of mixing induced on the freshwater when first entering the bay. It is concluded that the estuarine plume of Maputo Bay is in fact arrested during spring tide due to the large mixing inhibiting density currents and is released when mixing decreases, inducing stratification and baroclinic circulation. The potential energy stored in the bay is larger for a larger discharge of the Maputo River.